Renewable energy resources assessment in San Andres Island: An evaluation of wind, solar, biomass, tidal and wave resources, its reach, and future role in a more sustainable generation system (2022)
Estudio de los recursos de energías renovables para la isla de San Andrés y su complementariedad simulación de generación energetica de los mismos.